2020
DOI: 10.22159/ijap.2020v12i2.36477
|View full text |Cite
|
Sign up to set email alerts
|

Equivalence Study of Immediate Release Tablets of Beta Blocker Drug

Abstract: Objective: The therapeutic equivalence of generic brands is a great challenge for manufacturers. This study aimed to evaluate the bioequivalence of four different generic brands of atenolol tablets under biowaiver conditions. Methods: Physiochemical properties of the tablet products namely uniformity of weight, hardness, disintegration, and drug content were assessed. The dissolution profiles of atenolol tablets were conducted in pH 1.2, 4.5, 6.8 and 7.6 buffers using USP dissolution apparatus II. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Zero order First order Higuchi Hixon-Crowell Korsmeyer-peppas Comparing the R 2 values of all the formulations First order and Higuchi model showed the better fitting of data. The first order produced greater correlation of all formulations (R 2 =0.987 to 0.998 of) than all other models which indicated that the release of drug from the formulated tablets followed first order release kinetics that is the release is directly proportional to the concentration of the drug (10,11) .…”
Section: Formulationmentioning
confidence: 93%
See 3 more Smart Citations
“…Zero order First order Higuchi Hixon-Crowell Korsmeyer-peppas Comparing the R 2 values of all the formulations First order and Higuchi model showed the better fitting of data. The first order produced greater correlation of all formulations (R 2 =0.987 to 0.998 of) than all other models which indicated that the release of drug from the formulated tablets followed first order release kinetics that is the release is directly proportional to the concentration of the drug (10,11) .…”
Section: Formulationmentioning
confidence: 93%
“…The data obtained from the in vitro release study were analyzed using linear regression method according to the specified equations of zero order, first order, higuchi model, hixon-crowell model and korsmeyer-peppas model. Different plots were made such as cumulative % drug release vs. time (Zero order kinetic model); log cumulative of % drug remaining vs. time (First order kinetic model); cumulative % drug release vs. square root of time (Higuchi model); cube root of drug % remaining vs. time (Hixson-Crowell cube root law) and log cumulative % drug release vs. log time (Korsmeyer-Peppas model) (10,11) .…”
Section: Drug Release Kinetic Studymentioning
confidence: 99%
See 2 more Smart Citations